Features of dense plasma formation in the reflex discharge on gas-metal mixes - Kovtun, Yu.V. (Вопросы атомной науки и техники, 2013)
The paper briefly summarizes the data from studies of multicomponent gas-metal plasma in a pulsed reflex discharge. The processes of injection of sputtered-and-ionized working materials (Ti, Mo, W, U) into the reflex discharge plasma have been considered in the framework of the steady-state model. The measured data on the rotational velocity of the gas-metal multicomponent plasma formed in the reflex discharge correlate with the critical ionization velocity (CIV) values. Стисло підсумовані авторські дані по дослідженню багатокомпонентної газометалевої плазми імпульсного відбивного розряду. Розглянуто процеси, пов'язані з введенням робочої речовини (Ti, Mo, W, U) у плазму відбивного розряду за рахунок розпилюючого механізму для стаціонарної моделі. Результати вимірювання швидкості обертання газометалевої багатокомпонентної плазми, утвореною у відбитому розряді, корелюють з критичною швидкістю іонізації, CIV. Кратко суммированы авторские данные по исследованию многокомпонентной газометаллической плазмы импульсного отражательного разряда. Проведено рассмотрение процессов ввода рабочего вещества (Ti, Mo, W, U) за счет распылительного механизма и его ионизации в плазме отражательного разряда для стационарной модели. Результаты измерения скорости вращения газометаллической многокомпонентной плазмы, образованной в отраженном разряде, коррелируют с критической скоростью ионизации, CIV.